Quantitative analysis of cryomilled nanocrystalline Ti-6Al-4V alloy powder by X-ray diffraction - Oh, M.; Yu, H. K.; Lee, J. H.; Oh, M. C.; Jung, S. H.; Ahn, B. (Archives of Metallurgy and Materials, 2018)
A nanocrystalline Ti alloy powder was fabricated using cryomilling. The grain size and lattice strain evolution during cryomilling were quantitatively analyzed using X-ray diffraction (XRD) based on the Scherrer equation, Williamson-Hall (W-H) plotting method, and size-strain (S-S) method assuming uniform deformation. Other physical parameters including stress and strain have been calculated. The average crystallite size and the lattice strain evaluated from XRD analysis are in good agreement with the result of transmission electron microscopy (TEM).
Keywords: Cryomilling; Nanocrystallines; Physical parameters; Scherrer equations; Size-strain plot method; Stress and strain; Ti alloys; Uniform deformation; Cryomilling; Nanocrystalline; Size-strain plot method; Ti alloy; X-ray diffraction